Stability of typologies produced on the basis of repeated measurement with the role relationship and the name generator approach - Kogovšek, Tina (Metodološki zvezki, 2009)
In measuring ego-centered social networks, two general approaches can be distinguished. A very simple way to evaluate membership in a social network is to ask an ordinary survey question where response categories are types of relationships (e.g., partner, parents, children, friends, etc.). This approach (usually called the role relation(ship) approach) is very appealing as it saves time and money. However, information obtained by this approach is very limited. Most often, when evaluating ego-centered networks, the name generator approach is used. The list of egos (respondents) is obtained in the first step. In the second step, existing ties are identified - all alters with whom the focal ego has some sort of relationship. When all ties have been identified, the contents and the characteristics of ties are assessed. In most cases the characteristics of the alters are also measured. The name generator approach yields more data and is also of higher quality. However, it is time and money consuming, and it requires either considerable effort from respondents, when it is applied in self-administered mode, or complex coordination between interviewer and respondent, when it is applied in personal interviews (e.g., Kogovšek et al., 2002). In a series of studies (e.g., Hlebec and Kogovšek, 2005; Kogovšek and Hlebec, 2005; Kogovšek and Hlebec, 2008), network composition was estimated using both approaches. Test-retest and split-ballot experiments on convenience samples of respondents were used to assess the stability of network composition. Findings show that, with some caution, the two approaches are comparable. In the present paper this line of research is taken a step further. Typologies of social support networks are produced by hierarchical clustering on the basis of network composition, estimated by both approaches. Overall stability of typologies as well as stability of clustering of individual respondents is studied by means of simple descriptive analyses and by discriminant analysis. The results show that the overall stability of typologies is relatively high -two to three cluster groups are obtained in each analysis. However, the typologies seem to be more stable in one experimental group. Also the stability of clustering for individual respondents seems quite high as 73% to 85% of respondents were correctly classified. Incorrectly classified respondents were also studied, but their characteristics may well reflect the specific characteristics of the sampling procedure rather than some other systematic factor.
Keywords: Družbena omrežja; Social networks; Analiza omrežij; Network analysis; merjenje